2020
DOI: 10.1016/j.bbr.2019.112339
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-androgenic steroid abuse and cognitive impairment: Testosterone IMPAIRS biconditional task performance in male rats

Abstract: Our goal is to understand the consequences of anabolic-androgenic steroid (AAS) abuse on cognitive function, using rats as a model. There is relatively little research on how AAS abuse impacts cognition. In the present study, rats were tested for their ability to use contextual information to guide decision-making in biconditional discrimination. The Stroop task is a classic human test for contextual decision-making. In rodents, biconditional discrimination challenges subjects to use contextual cues in the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In humans, rodents and birds, T treatment reduces behavioural flexibility [1][2][3][4][5][6][7][8] . In these studies, T does not impair learning but rather promotes persistence of a learned strategy and impairs shifting to a novel more advantageous one 9 . The prefrontal cortex (PFC), including the mPFC and orbitofrontal cortex (OFC), is essential for behavioural flexibility 10 .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In humans, rodents and birds, T treatment reduces behavioural flexibility [1][2][3][4][5][6][7][8] . In these studies, T does not impair learning but rather promotes persistence of a learned strategy and impairs shifting to a novel more advantageous one 9 . The prefrontal cortex (PFC), including the mPFC and orbitofrontal cortex (OFC), is essential for behavioural flexibility 10 .…”
Section: Introductionmentioning
confidence: 72%
“…Our main objective was to determine whether inhibition of androgen synthesis or GDX increased behavioural flexibility. T reduces behavioural flexibility, however in most previous studies T levels were increased to supraphysiological levels 4,6,9 . For example, Wallin and Wood administered a high dose of T to intact male rats and found impairments in set shifting and reversal learning 4 .…”
Section: Abi Decreases Persistence In Set-shifting and Reversal Learningmentioning
confidence: 92%
“…As a result, they reduced dopaminergic function and disrupted the androgen regeneration system. All of these events led to decreased neuronal flexibility and affected learning and memory [24]. In this regard, the results of the studies demonstrated that long-term use of AAS led to a decrease in the number of healthy cells in the cortex, cerebellum, and hippocampus [2].…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, the results of the studies demonstrated that long-term use of AAS led to a decrease in the number of healthy cells in the cortex, cerebellum, and hippocampus [2]. The injections of 7.5 mg/kg testosterone for 14 days also impaired learning in rats, thereby increasing the rate of cognitive impairment [24]. However, the mechanism of exercise activity has been known to increase neurotrophins, reduce oxidative stress, improve vascular circulation, and increase neuronal plasticity in the central nervous system [25].…”
Section: Discussionmentioning
confidence: 97%
“…However, other authors reported that, in castrated male rats, high androgen levels exacerbate ischemic damage [ 25 ]. Similarly, a more recent study showed that chronic high-dose T administration impairs cognitive flexibility in a rat animal model [ 26 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%